PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS POTENSI LOKAL MATERI ASAM BASA DI KELAS XI MIA SMA NEGERI 2 KUPANG - Dre, Stefanus; Wariani, Theresia; Tukan, Maria Benedikta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
The aim of this research is to determine the validity of the Student Worksheet (LKPD) based on the local potential of acid-base material, to find out the learning outcomes of students after using the Student Worksheet (LKPD) based on the local potential of acid-base material that was developed, to find out the response of students to the Student Worksheet (LKPD) based on the local potential of acid-base material that was developed. This type of research is research and development (Research & Development). The instruments used in this research were validation sheets, test sheets, and student response questionnaires. The material expert validation results obtained were in the valid category with a percentage of 82%, the media expert validation results obtained were in the very valid category with a percentage of 86%, the student learning outcomes for the knowledge (KI-3) and skills (KI-4) aspects were declared complete with the overall average completeness of learning outcomes obtained from 20 students being 86.3, and the percentage of student responses obtained was 91%.